EFFECT OF IONIC LIQUIDS BASED PRETREATMENT OF OIL PALM FRONDS ON THE PROPERTIES OF BIOCOMPOSITES - MAHMOOD, HAMA YOUN (2017)
Ionic liquids (ILs) pretreatment has emerged as the promising technology toward environmentally benign conversion of lignocellulosic residues into cellulose-rich fiber as sustainable raw material for biocomposite manufacturing. The principal objective of the present study was to evaluate the impact of ILs based pretreatment of oil palm fronds (OPF) residue on the mechanical, thermal and water absorption properties of the biocomposites. The OPF fiber was pretreated with ILs [bmim][Cl] (1-butyl-3- methylimidazolium chloride) and [ emim] [ dep] (1-ethyl-3-methylimidazolium diethyl phosphate) prior to prepare biocomposite board by using compression molding technique. Mechanical, thermal and water absorption properties of the biocomposites prepared from ILs treated OPF fibers were investigated and compared with those fabricated from untreated fiber. To understand the effect of ILs pretreatment on OPF fiber, lignocellulosic characterization, FTIR, PXRD, FESEM and TGA analysis were performed. Influence of ILs pretreatment on the thermal degradation kinetics of the biocomposite panels by employing activation energy approach was also studied.